(untitled) (Indian Journal of Public Health Research & Development, 2026)
Introduction: Urban and rural diets in India are subject to influences like income, food availability, and life styles. As school teachers are also health promoters and role models for their students and communities, this study was set to identify the dietary patterns of urban and rural school teachers in Guntur district of Andhra Pradesh, India along with comparison of anthropometrics and Diet Related Non-Communicable Disease (DRNCDs). Methods: This descriptive study involved all teachers of five schools each from rural and urban mandals of Guntur district selected by simple random sampling. A predetermined questionnaire covering various aspects of diet, socio – demographic variables and anthropometric measurements like height, weight, BMI and waist hip-ratio were administered to each teacher after taking an informed consent. Data was entered in MS excel and presented in tables and graphs. Important findings were subjected to tests of significance like Chi square test at 5 % Level of Significance. Results: Chronic non communicable illnesses were present in 27.6% of the rural teachers and 66.0% of urban teachers (Chi square 16.5%, p value < .0001, OR 5.1, 95% CI 2.1 to 12.5). DRNCDs were present in 27 (46.6%) rural teachers and 24 (45.3%) urban teachers.86.8% of the male teachers and 43.1% of the female teachers were obese according to their BMI (Chi Square 22.93, p value <0.0001). Normal BMI was not seen in any of them. Urban teachers and families were indulging more in junk foods probably due to more access (Chi Sq 5.9, p 0.01). 66.7% of all the teachers were unsure if their diets were complete or healthy. Discussion: Significant gender differences were found in the anthropometric measurements which were more adverse in the males. Important dietary patterns based on intake of breakfast daily, beverages, spicy foods, junk foods, fresh fruits and vegetables, nutritional, ayurvedic and homeopathic supplements. Conclusion: Knowledge of dietary patterns enables identification of unhealthy practices prevalent in the community. There is a need for educating the communities about balanced and healthy diets.